Sistem Pakar Diagnosa Gejala Kecanduan Game Online dengan Metode Backward Chaining - Farhan Hamdallah (Cakrawala Repositori IMWI, 2020)
In the last decade, there have been people whose style of play effects are online. This style of online gamewill be a very middle thing, because this opium could be a husband with no real life, nor cause death. There are suspected cancer victims online games need to consult this problem on. But many factors are pakah to come to pakkes, such as lazy, no time, our timing so cost. Therefore, the system of cancer experts diagnose online games using backward chaining in the hope that can consult with experts do not need to come to the doctor.